Waste to energy: air pollutant emissions from the steam boilers using recycled waste wood - Tsai, Jiun Horng; Lin, Kuo Hsiung; How, Vivien; Deng, Yu An; Chiang, Hung Lung (Taiwan Association for Aerosol Research, 2021)
In Taiwan, combustible wood mostly comes from waste pallets and scrap packaging materials discarded by factories, which produced a total of 278,067 tons of waste wood in 2019. In this study, the heat value of waste wood was 18.3 ± 1.07 MJ kg–1. The measured volatile fraction was 76.5 ± 7.34%, the fixed carbon was 15.7 ± 3.19%, the ash content was 2.96 ± 2.45%, and the moisture content was 21.6 ± 10.2%. The proportions of the elemental constituents in the waste wood were 45.3 ± 4.95%, 46.9 ± 3.94%, 5.9 ± 0.44%, 0.21 ± 0.17%, 0.29 ± 0.26%, and 0.02 ± 0.02% for carbon, oxygen, hydrogen, sulfur, nitrogen, and chlorine, respectively. The average boiler capacity was 11.5 ± 6.84 ton hr–1, the average fuel consumption of the boilers was 1.47 ± 1.81 ton hr–1, the average operating temperature of the boilers was 853 ± 228°C, the average steam generation of the boilers was 7.63 ± 5.97 ton hr–1, and the average exhaust flow rate was 246.6 ± 200.9 m3 min–1. The main air pollution control systems used in the waste wood combustion boilers were systems combining a cyclone, a baghouse and a scrubber (37.8%), a cyclone and a baghouse (28.4%), a cyclone and a scrubber (10.2%), and systems using a baghouse only (9.8%). Based on our fuel consumption data, the air pollutant emission factors were 0.71 ± 1.44 kg per ton of wood for PM, 0.86 ± 1.47 kg per ton of wood for SOx, and 5.24 ± 9.56 kg per ton of wood for NOx. In July 2022, new emission standards for boilers will be implemented, and emission reductions of at least 30% for PM, 35% for NOx and 7% for SO2 will be required.